Cross section of pseudoscalar meson photoproduction within the ELA - Quirós, J. J. (2015)
We study the contributions of background and resonance terms to the total cross section of photoproduction of mesons off the free nucleon. The model we use is consistent and based on an effective Lagrangian approach (ELA) which includes nucleon Born terms, vector meson exchange terms, and nucleon resonances. The interaction Lagrangians are chiral symmetric, gauge invariant and crossing symmetric. The results we obtain are compared to available experimental data and agreement is found in the energy region from threshold up to 0.55 GeV in the case of π photoproduction. We outline the possibility to extend this calculation to the case of η meson photoproduction.